2021
DOI: 10.1111/jonm.13501
|View full text |Cite
|
Sign up to set email alerts
|

Nurse staffing, missed care, quality of care and adverse events: A cross‐sectional study

Abstract: Aim: This study aimed to illustrate the relationship between nurse staffing and missed care, and how missed care affects quality of care and adverse events in Thai hospitals.Background: Quality and safety are major priorities for health care system. Nurse staffing and missed care are associated with low quality of care and adverse events.However, examination of this relationship is limited in Thailand.Methods: This cross-sectional study collected data from 1188 nurses in five university hospitals across Thaila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 39 publications
0
31
2
1
Order By: Relevance
“…Missed care is an important issue as it reflects delayed or ignored care (Sworn & Booth, 2020) and result in poor patient outcomes (Phelan & Kirwan, 2020). Missed care degrades patient care quality and causes problems in patient safety (Nantsupawat et al, 2022), indicating the managerial importance of reducing it. Hence, missed care is also a critical outcome that needs to be addressed in nursing workplaces and therefore should be included in our study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Missed care is an important issue as it reflects delayed or ignored care (Sworn & Booth, 2020) and result in poor patient outcomes (Phelan & Kirwan, 2020). Missed care degrades patient care quality and causes problems in patient safety (Nantsupawat et al, 2022), indicating the managerial importance of reducing it. Hence, missed care is also a critical outcome that needs to be addressed in nursing workplaces and therefore should be included in our study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nurses are the front‐line workers who have the most contact with patients and provide the most medical services, and they are an important force in ensuring patient safety (Nantsupawat et al, 2022). However, due to limited funds, insufficient staff and resources and strained nurse–patient relationships, nurses face increasing pressure (Alsubhi et al, 2020), making it difficult for them to fulfil all their full nursing responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…47.8%–98% of nursing staff reported that they had one or more tasks uncompleted (Du et al, 2020; Jones et al, 2015; Lake et al, 2020), which can have negative impacts at the patient and institution levels (Schubert et al, 2021). Missed nursing care can result in lower quality nursing care and more adverse events, including medication errors, infections, increased patient mortality, poor prognosis, patient complaints and verbal abuse of nurses, etc (Aiken et al, 2014; Kalánková et al, 2020; Nantsupawat et al, 2022; Schubert et al, 2021). In addition, it reduces nurses' job satisfaction and increases their intention to leave, which increases their turnover rate, thereby affecting the quality of nursing services (Kalisch, Landstrom, & Williams, 2009; Kalisch & Lee, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nursing workforce plays an integral part in healthcare, improves patient outcomes and promotes good health (Poghosyan & Maier, 2022). In recent years, with the rapid development of the nursing industry and the changing needs of patients, nursing managers have faced challenges in encouraging clinical nurses to ensure high standards of patient care and safety to promote hospital performance and quality (Nantsupawat et al, 2022). Nursing managers are crucial actors in the healthcare environment and play an essential role in developing a comfortable working atmosphere where nurses can provide safe, high-quality care to realize the organizational aims of a hospital and ensure good health outcomes (Labrague et al, 2018).…”
Section: Introductionmentioning
confidence: 99%